Molecular detection of equine herpes virus-1 in local horses (Equus feruscaballus) and donkeys (Equus asinus) - Al-Ajeeli, Karim Sadun Ali (The Iraqi Journal of Veterinary Medicine, 2018)
Equine herpsvirus type1 was classified as a member of the subfamily Alphaherpesvirinae. It was reported to cause respiratory, reproductive and neurologic infection in horses. The reproductive form of the disease induces abortion in pregnant mare, while the neurologic form is associated with paralysis of infected horses. This study was designed for molecular detection of Equine herpsvirus type1 by polymerase chain reaction. Blood buffy coat samples were collected from 25 horses (Equus feruscaballus) and 25 donkeys (Equus asinus) admitted to local private veterinary clinics around Baghdad and Baaquba cities. DNA was extracted from such samples by the use of DNA extraction kit of COLLECTAGENET .The samples were subjected to conventional PCR test using specific primers for gB gene of equine herepesvirus-1. Forward primer (F) (5’ TAACTGAGATCT AACCGAC 3’) and reverse primer (R) (CATATATAGCTATCACGTCC 3’). One buffy coat sample from aborted mare and one buffy coat sample from a donkey suffering from acute respiratory clinical signs were inoculated in mice to follow the fate of equine herepesvirus-1in nasal turbinates, cervical lymph nodes and lungs of these mice. The results showed that only 4 samples from horses and 2 samples from donkeys were positive to polymerase chain reaction. Experimentally infected mice did not show any clinical signs but they were positive to polymerase chain reaction, and the virus easily terminated, probably due to low dose of the virus and host specificity. It can be concluded that local horses and donkeys, somewhere have had infected with equine herepesvirus-1, and became latent carriers for the virus. Furthermore, microbiological and epidemiological studies on local Equine herpsvirus type1 and Equine herpsvirus type 4 are recommended.